Pengaruh Mata Kuliah Kewirausahaan, Self Efficacy, E-Commerce, Dan Sistem Informasi Akuntansi Terhadap Minat Berwirausaha Mahasiswa Akuntansi Politeknik Negeri Padang - Yuni Putri; Nurul Fauzi; Desi Handayani (Politeknik Negeri Padang, 2024)
Unemployment is one of the serious problems that is still difficult to overcome in Indonesia. Many young people are unemployed, so cultivating an entrepreneurial spirit can be an alternative to overcome limited employment and reduce the number of unemployed. This study aims to determine the influence of entrepreneurship, self-efficacy, e-commerce, and accounting information systems courses on the entrepreneurial interest of Accounting students of Padang State Polytechnic. This research is quantitative research. The sample collection technique uses purposive sampling, namely accounting students who have taken entrepreneurship and accounting information systems courses. The number of samples used was 176 samples. Data collection is carried out by distributing questionnaires through Google Forms.The data analysis technique used in this study is using hypotheses and coefficients of determination using the SPSS program version 25. The results of the study showed that e-commerce did not effect students' entrepreneurial interest, while entrepreneurship, self-efficacy, and accounting information system courses had an influence on the entrepreneurial interest of Accounting students of Padang State Polytechnic.